Sweet as Vanilla hartii: Evidence for a nectar-rewarding pollination mechanism in Vanilla (Orchidaceae) flowers - Watteyn, Charlotte (2023)
Little is known about the pollination mechanisms of species belonging to the genus Vanilla (Orchidaceae). Both autonomous self-pollination and animal-mediated pollination mechanisms seem to exist amongst the Vanilla species, yet few studies provided real evidence on pollination events. The aim of this study was to better un- derstand the pollination mechanism of Vanilla hartii. Four V. hartii populations were selected within our study area in southern Costa Rica to observe pollination events and identify the natural pollinators of this Neotropical Vanilla species. We tested for nectar presence, analysed nectar composition, and examined floral fragrances. Furthermore, we identified floral visitors and documented their behaviour, quantified fruit set during two years, and compared morphological traits of flowers and their visitors. Sampled flowers contained 1.85 ± 1.07 μL nectar that averaged 34.79% sugar, dominated by sucrose. We observed orchid bees belonging to the genus Euglossa entering the tube formed by the labellum to search for nectar, indicated by their extended proboscis and prolonged visits, some of which exited the labellar tube with pollen masses attached to their scutellum. Combining our behavioural and phytochemical data, we demonstrate the presence of a nectar-rewarding pollination mechanism in the genus Vanilla that shows a higher natural fruit set compared to deceptive Va- nilla species. An overview of the pollination mechanisms known so far provides insights into the potential evolution of reproductive strategies within this commercially important orchid genus.